Factors associated with resilience among parents of children with autism spectrum disorder: A systematic review - Nora Saliza Md Salim; Idayu Badilla Idris; Norazlin Kamal Nor; Syakirah Roslan; Nafisah Abdul Rashid; Roszita Ibrahim; Fairuz Nazri Abd Rahman (PLoS ONE, 2026)
Parents of children with autism spectrum disorder (ASD) experience ongoing caregiving demands and challenges that may contribute to their general well-being. Research has shown that resilience enables parents to adapt to these challenges; however, existing evidence on associated factors toward resilience among these parents remains fragmented. This systematic review aimed to identify factors associated with resilience among parents of children with ASD. We conducted a PRISMA 2020-guided systematic review on studies published between January 2019 and May 2025 using Web of Science, Scopus, and PubMed by applying predefined search terms and Boolean operators. Studies examining factors associated with resilience among parents of children with ASD aged under 18 years were included in this review. We also used the Mixed Methods Appraisal Tool 2018 to assess the quality of these studies. Findings were synthesised narratively using thematic analysis. From the 13 selected studies, five themes were identified as determinants of resilience among parents, i.e., sociodemographic and economic factors; child-related characteristics; parenting well-being and distress; psychological factors and coping styles; and social support and family relationships. Most included studies were cross-sectional and utilised different measurement tools, which may limit causal inference and comparability. As a conclusion, parental resilience was found to be influenced by psychological, social, and contextual factors. Strengthening coping resources and social support may enhance parental adaptation and family well-being. Along these lines, multi-level and culturally sensitive interventions are thus needed to inform strategies to foster resilience among parents of children with ASD. The review was registered with PROSPERO (CRD420251034348). The author(s) received no specific funding for this work.